Phase formation in cemented carbides prepared from WC and stainless steel powder – An experimental study combined with thermodynamic calculations. (April 2019) - de Oro Calderon, Raquel; Agna, Alessandra; Gomes, Uilame Umbelino; Schubert, Wolf-Dieter
Abstract: Cemented carbides prepared from mixes of WC and stainless steel powder have been proposed as possible alternatives to WC-Co. However, phase formation in such systems is not well described in the literature, in particular with regard to the possible formation of Cr-carbides. In this work, cemented carbides have been prepared from batches of coarse WC powder and 20 wt% AISI 360 L stainless steel powder, considering different carbon black additions to vary the final carbon contents to 4.9, 5.64, 5.75 wt% C. Both experimental results and thermodynamic calculations show that no classical two phase area – containing only WC and metallic binder- can be expected in these alloys. (Cr, Fe)-carbides are observed at all carbon contents in equilibrium with eta phases and binder, and at the highest carbon content also with graphite. As a consequence of the formation of (Cr, Fe)-carbides the amount of metallic binder decreases significantly, and the composition of the binder changes drastically. The binder phase in the sintered materials constitute an Fe-15Ni alloy with about 5 wt% Cr and 2 wt% W in solid solution, which is more similar to a maraging steel rather than a stainless steel. Both thermodynamic calculations and experimental results confirm that the maximum amount of Cr that can be retained in the metallic binder is around 5 wt% Cr which implies that, after sintering, the stainless steel properties will be lost.